2018
DOI: 10.1155/2018/6287932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fine Particulate Matter onPseudomonas aeruginosaAdhesion and Biofilm FormationIn Vitro

Abstract: Respiratory infections of Pseudomonas aeruginosa are a major cause of mortality and morbidity for hospitalized patients. Fine particulate matter (FPM) is known to have interactions with some bacterial infection in the respiratory system. In this report, we investigate the effect of different concentration of FPM on P. aeruginosa attachment and biofilm formation using in vitro cell culture systems. P. aeruginosa were cultured to form mature biofilms on hydroxyapatite-coated peg and the number of bacteria in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…In this study we show that simultaneous inoculation of S. aureus and biologically relevant concentrations of BC causes increased infection of murine lungs and increased nasopharyngeal colonization. These new data agree with our previous observations with S. pneumoniae exposed to BC (Hussey et al, 2017) and confirm a wider phenomenon of the impact of BC on bacterial respiratory tract colonization, that also been recently shown with other types of particulate pollutant (Liu et al, 2019;Shears et al, 2020;Woo et al, 2018;Yadav et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In this study we show that simultaneous inoculation of S. aureus and biologically relevant concentrations of BC causes increased infection of murine lungs and increased nasopharyngeal colonization. These new data agree with our previous observations with S. pneumoniae exposed to BC (Hussey et al, 2017) and confirm a wider phenomenon of the impact of BC on bacterial respiratory tract colonization, that also been recently shown with other types of particulate pollutant (Liu et al, 2019;Shears et al, 2020;Woo et al, 2018;Yadav et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In this study we show that simultaneous inoculation of S. aureus and biologically relevant concentrations of BC causes increased infection of murine lungs and increased nasopharyngeal colonisation. These new data agree with our previous observations with S. pneumoniae exposed to BC (Hussey et al, 2017) and confirms a wider phenomenon of the impact of BC on bacterial respiratory tract colonisation, that also been recently shown with other types of particulate pollutant (Liu et al, 2019; Shears et al, 2020; Woo et al, 2018; Yadav et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study to pre-grow the bacteria with PM prior to inoculation. All previous studies have either pre-exposed the host to PM or inoculated PM and bacteria together(Liu et al, 2019; Shears et al, 2020; Woo et al, 2018; Yadav et al, 2020). These publications hypothesised that increased bacterial colonisation was due to PM binding to the bacteria thereby promoting transmission throughout the respiratory tract, or PM providing metabolites to support bacterial growth or PM-mediated toxicity damaging epithelial integrity (Liu et al ., 2019; Yadav et al ., 2020; Shears et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Liu et al (2018) reported that ROS induced by PM 2.5 activated the AKT/STAT3/NF-κB pathway through IL-6 paracrine signaling, which then upregulated the expression of intercellular adhesion molecule-1 (ICAM-1, an important glycoprotein on the cell surface) in the lung to increase the adhesion of pathogens to the airway epithelium (Figure 3B). Woo et al (2018) also found that PM 2.5 could enhance the adhesion of P. aeruginosa to epithelial cells, the mechanism of which depended on the increased bacterial surface hydrophobicity and damaged human cell plasma membrane by PM 2.5 . Tight junctions (TJs) are the significant protein complexes at cell-cell interfaces that connect adjacent cells with each other to form lung epithelial barrier against pathogens (Schlingmann et al, 2015).…”
Section: Defective Airway Epithelial Host Defense Functionsmentioning
confidence: 87%